Trace elements and organochlorine pollutants in selected fish species from Lake Phewa, Nepal. Issue 3 (16th March 2017) - Rosseland, Bjørn Olav; Teien, Hans-Christian; Basnet, Suresh; Borgstrøm, Reidar; Sharma, Chhatra Mani
ABSTRACT: Lake water and fish livers and gills of sahar ( Tor putitora ), spiny eel ( Mastacembelus armatus ), African magur ( Clarias gariepinus ), and tilapia ( Oreochromis niloticus ) from Lake Phewa, Nepal, were assessed for the concentrations of trace metals/elements and persistent organic pollutants. The lake water was neutral with low ionic and metallic concentrations as compared to high-altitude lakes of Nepal. The four elements Cu, Zn, Se, and Cd had highest concentrations in livers, indicating uptake from diet, whereas four other metallic elements Cr, Mn, Ni, and Pb had highest concentrations in gills, indicating uptake from lake water. O. niloticus tended to have most of trace metals in the liver at higher concentrations than the other species but significant differences among the different species were found only for Mn, Ni, and Zn in the gills. A pilot study on the concentrations of persistent organic pollutants in muscle revealed that dichlorodiphenyltrichloroethane and related compounds were the dominant organochlorine pesticides, having highest concentrations in C. gariepinus and lowest in O. niloticus .